Unilateral brain damage after prolonged hemiconvulsions in the elderly associated with theophylline administration. Issue 6 (June 1992) - Mori, H; Mizutani, T; Yoshimura, M; Yamanouchi, H; Shimada, H
Abstract : The brains of 14 elderly patients who died after status epilepticus were examined pathologically. Three of the 14 patients showed unilateral brain damage which corresponded to the side of the seizures, and the lesions were thought to be caused by seizures. In these three and two other patients, no causative lesion related to the seizures was found. In these five patients, status epilepticus occurred during theophylline therapy and thus the seizures in these five patients were assumed to be induced by theophylline. In the three patients with unilateral brain damage, the damage was seen in the hippocampus, amygdala and thalamus in two patients, while in the third, the whole hemisphere was damaged, including the hippocampus, amygdala, thalamus, basal ganglia and cerebral cortex. The distribution of pathological changes within the thalamus was described. It is suggested that the thalamus was primarily affected by seizures, rather than by secondary degeneration from the cortex.